Assessment of schedulable potential for user-side resources participating in demand response based on improved G1 method using SRC - Wu, Hairu; Yang, Maotao; Wu, Rong; Fan, Qingchuan; Chen, Xiangyuan; Xiao, Jianhong (Frontiers in Energy Research, 2023)
In order for user-side resources to participate in demand response (DR) more accurately, schedulable potential assessment of user-side resources is required. An improved G1 method using Spearman rank correlation (SRC) has been proposed to evaluate the schedulable potential for user-side resources. First, the DR potential evaluation indicator is established on the basis of the characteristics of user-side resources. Second, the resource potential score is calculated by using the improved G1 method using SRC, and the DR potential is obtained. Finally, the resource schedulable capacity of a certain region is obtained. The results show that the method realizes the potential evaluation of user-side resources in a region to participate in DR and provides data support for the power supply company to reasonably schedule user-side resources. Moreover, when compared with existing methods, the proposed method greatly improves the availability of the power company–scheduled regional resources to participate in DR.